Dynamics and optical manipulation of nuclear spin in self assembled (InGa)As/GaAs quantum dots - Flisinski, Karl (Technische Universität Dortmund, 2014)
Nuclei and electrons trapped in quantum dots create a strongly interacting spin system due to the strong localization of electrons in quantum dots. Due to strain in self-assembled (In,Ga,As)GaAs quantum dots quadrupole interactions appear which have a significant influence on the nuclear spin system. Therefore it is no longer possible to describe the nuclear spin system as one system with certain characteristics like a buildup time and decay time. Instead, in the case of strain the nuclear spin system can be separated into two subsystems, one with a nuclear spin state |±1/2⟩ which is weakly influenced by quadrupole interactions and the other with nuclear spin states |±3/2⟩, |±5/2⟩,… which is strongly influenced by quadrupole interactions. Each subsystem possesses different characteristic buildup and decay times of dynamic nuclear polarization generated by circular polarized light excitation of the quantum dots. A fast decay mechanism for polarized nuclei occurred during an interruption of the excitation beam for quantum dots with a single resident electron on a nanosecond scale. In relation to this phenomenon strong differences for the dynamic nuclear polarization are detected when either pulsed- or CW-lasers are used for excitation due to the short excitation time in relation to the repetition rate of the pulsed-laser. Further a new effect of optical pumping of nuclear spins in quantum dots is observed. The new effect, called resonant nuclear spin pumping, is observed in a magnetic field oriented perpendicularly to the excitation light beam (Voigt geometry). It creates a nuclear polarization perpendicular to the externally applied magnetic field.
Keywords: Hanle effect; Nuclear magnetic resonance (NMR); Nuclear spin cooling; Negative circular polarisation (NCP); Kramer's doublets; Self assembled quantum dots; Overhauser field; Nuclear spin fluctuation; 530